Analysis of a multistandard modem operation using constellation diagram, data transmission and error rate measurement / Noor Azura Aridi - Aridi, Noor Azura (1999)
This project presents the analysis of modem VM 24/EV that use different speeds by using constellation diagram. The objective in this paper is to study the modem operation, the manual and automatic connection on switched line, data flow control, effect of noise in connection and error rate measurement using VM24 and data tester.